4-Formylphenyl 2,3,4,6-tetra-O-acetyl-β-d-glucopyranoside - Heidelberg, Thorsten (International Union of Crystallography, 2011)
The pyranoside ring in the title compound, C(21)H(24)O(11), has a chair conformation with the substituted benzene ring occupying an equatorial position. The crystal packing is dominated by C—H⋯O interactions that lead to the formation of supramolecular layers in the ab plane.